2014
DOI: 10.1186/1471-2121-15-33
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial localization of the OAS1 p46 isoform associated with a common single nucleotide polymorphism

Abstract: BackgroundThe expression of 2′-5′-Oligoadenylate synthetases (OASs) is induced by type 1 Interferons (IFNs) in response to viral infection. The OAS proteins have a unique ability to produce 2′-5′ Oligoadenylates, which bind and activate the ribonuclease RNase L. The RNase L degrades cellular RNAs which in turn inhibits protein translation and induces apoptosis. Several single nucleotide polymorphisms (SNPs) in the OAS1 gene have been associated with disease. We have investigated the functional effect of two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…HeLa (ATTC: CCL-2) and HT1080 (ATCC: CCL-121) cells were cultured as adherent cells at 37 • C with 5% CO 2 in Dulbecco's modified Eagle's medium with high glucose and with sodium pyruvate (Life Technologies Europe BV, Naerum, Denmark) with added 10% sterile-filtered fetal bovine serum (FBS) (Sigma-Aldrich, Søborg, Denmark ) and 1% Penicillin-Streptomycin (Pen-Strep) solution (Sigma-Aldrich) at 37 • C and 5% CO2. The human HT1080 and HeLa cell lines used have the AG genotype and the AA genotype, respectively, regarding the SNP rs10774671 [9]. For interferon treatments, both HeLa and HT1080 cells were grown to~80% confluence and were treated with 1000 U/mL IFN-β or left untreated for 24-48 h before analysis.…”
Section: Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…HeLa (ATTC: CCL-2) and HT1080 (ATCC: CCL-121) cells were cultured as adherent cells at 37 • C with 5% CO 2 in Dulbecco's modified Eagle's medium with high glucose and with sodium pyruvate (Life Technologies Europe BV, Naerum, Denmark) with added 10% sterile-filtered fetal bovine serum (FBS) (Sigma-Aldrich, Søborg, Denmark ) and 1% Penicillin-Streptomycin (Pen-Strep) solution (Sigma-Aldrich) at 37 • C and 5% CO2. The human HT1080 and HeLa cell lines used have the AG genotype and the AA genotype, respectively, regarding the SNP rs10774671 [9]. For interferon treatments, both HeLa and HT1080 cells were grown to~80% confluence and were treated with 1000 U/mL IFN-β or left untreated for 24-48 h before analysis.…”
Section: Cell Linesmentioning
confidence: 99%
“…The subcellular localization of the two OAS1 isoforms also seems to be different. We have previously observed that the OAS1 p46 isoform is localized in the mitochondria, whereas the p42 is more evenly distributed in the cytosol [9]. We have hypothesized that this difference could be due to the presence of a CaaX motif (C = Cysteine, a = aliphatic amino acid, X = terminal amino acid) in the C-terminal of only the p46 isoform, which could be important in directing the protein to the mitochondria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the molecular basis for this association is not well understood. In several studies, it was shown that polymorphisms in the OAS genes result in variations in enzyme activity by influencing basal enzyme activity[39], gene expression[17] or cellular localization[40]. …”
Section: Discussionmentioning
confidence: 99%
“…The comparative population analysis pointed to the 7 coding variants in PLG, TMPRSS11a, MBL2 and OAS1 with noticeable divergence in allelic frequencies between analyzed populations. [42] and multiple sclerosis [43], but a more recent study showed that this variant was found not to interfere with OAS1 enzyme activity [44].…”
Section: Comparative Population Analysismentioning
confidence: 98%